E-learning situation children with disabilities during the COVID-19 pandemic - Monanda, Adelia Pramudita; Padmawati, Retna Siwi; Azizatunnisa', Luthfi (BKM Public Health and Community Medicine, 2022)
Purpose: Online learning or e-learning is the solution to the COVID-19 pandemic. With this condition, the parents must accompany their children with disabilities in e-learning at home. The research aims to explore the situation of e-learning in children with disabilities. Methods: This qualitative study used a case study approach. Participants were recruited through the purposive sampling technique. There were 11 main participants, parents or learning companions of students with disabilities, and four supporting participants who were the Head of the Kapuas Regency Office, the Principal of the SLB Negeri 2 Kapuas, and one of the teacher representatives in each SLB Negeri 1 and SLB Negeri 2 Kapuas. Results: In the process of e-learning learning activities at SLB Negeri 1 and SLB Negeri 2 Kapuas, very few parents of children with disabilities can provide gadgets and limited internet access in the area where they live. Therefore, learning activities during the COVID-19 pandemic for children with disabilities were implemented using WhatsApp groups and teachers visiting each student's house. Parents must know and maintain their children's learning mood, invite children to do learning activities in a pleasant atmosphere, and parents must be able to divide their time between work and accompanying children to study. Conclusion: In its implementation, the course encounters obstacles; the role of teachers and parents is also very influential, so the e-learning method can run optimally through good cooperation between teachers and parents in educating and motivating disabled students during learning at home.